FAKTOR â FAKTOR YANG BERPENGARUH TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - Shelvi Amalia, 11.05.52.0134; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This study aims to examined and analyzed the effect of tax incentives and nontax factors to accounting conservatism on manufacturing companies listed in the Indonesia Stock Exchange. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2012-2014 that reported complete annual report and published in Indonesian Capital Market Directory. Samples are included in the criteria of this study were 38 companies using purposive sampling method. This research data analysis methods using the multiple linear regression analysis byÂ  SPSS 19. The results showed that profitability, leverage and size has significant positive effect on accounting conservatism. Tax incentives, earnings pressure, growth opportunities, and managerial ownership has no effect on accounting conservatism.Keywords: Accounting Conservatism, Tax Incentives, Earnings Pressure, Profitability, Leverage, Growth Oppotunities, Size, Manager Ownership